STUDY OF STAR FORMATIONS IN LAMBDA COLD DARK MATTER MODEL - Rasheed, Mariwan; Ameen, Mudaffer (Iraqi Journal of Science, 2024)
Star formation inside a box of size (120Mpc/h)3 was studied using Lambda Cold Dark Matter (ΛCDM) model by simulating one million dark matter particles and one million gas particles. The particles were simulated from early Universe, z=30 (450 million years) to z=0 (13.4 billion years).In the simulation galaxy clusters, voids and filaments were constructed at low redshift, z=0. Stars were formed from redshift z=5.99. The formations increased with decreasing redshifts but at some redshifs stars were not formed and the total number of star formed in the box was 28443 stars.The gadget-2 code was depended in the simulation and sixteen processors of high performance supercomputer of Nottingham University-England were used.